Classification and Translation of Idiomatic Expressions - Sazdovska Pigulovska, Milena; Gjurchevska Atanasovska, Katarina (Lambert Academic Publishing, 2020)
This book suggests a classification of idiomatic expressions on the basis of the manner of creation, the context of use and the level of formality, whereas special focus is put on literary idioms as well as on professional idioms. Furthermore, the authors discuss specificities of translating different types of idiomatic expressions and suggest applicable translation strategies in order to address the problem of inadequate translation of both culturally-specific and professional idioms. The insights presented in this book are based on contemporary theoretical concepts and on a corpus-based study of comparative examples. Additionally, by offering practical exercises, the book enables the users to practice and to master techniques and strategies for overcoming both classification and translation problems with an educational purpose: to raise awareness of what translation really means and the standards to be met.
Theory and Practice
Keywords: Idiomatic Expressions, classification, translation